PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWAKELAS VII8 SMP NEGERI 21 PEKANBARU - Revira Agustin; Sehatta Saragih; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is low of mathematics learning outcomes of class VII8 of 21 Junior High School Pekanbaru in first semester of the 2017/2018 academic year. Related to learning outcomes, one of the main factors affecting is the learning process. In line with it, the in order to improve student learning outcomes, it is necessary to improve the learning process. The type of this research is the Classroom Action Research that has purpose to improve the learning process and to increase student’s mathematic learning outcomes by applied the Problem Solving Strategy in Cooperative Learning. This research consists of two cycles that each cycle composed of 4 stages, such as planning, implementation, observation and reflection. At every end of a cycle, math achievement test will be held.The research instrument consists of learning devices that involve Syllabus, Lesson Planand Worksheet, and instrument data collector that involvethe observation sheet and math achievement test. The Observations collected through the observation sheet by narrative descriptive analysis and math achievement test by statistic descriptive analysis.The result of the research showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvementafter reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 12 person (27,27%), 23 person (52,27%) and 28 person (61,36%). Results of this research indicates that application of Problem Solving Strategy in Cooperative Learning can improve learning process and increase mathematics learning outcomes from the studentsof class VII8 of 21 Junior High School Pekanbaru in first semester of the 2017/2018 academic year at the subject matter of equation and linear inequalitiesof one variable.Key Words: Problem Solving Strategy, Cooperative Learning, Mathematics Learning Outcomes